2019
DOI: 10.1007/s10973-019-08836-y
|View full text |Cite
|
Sign up to set email alerts
|

Convective heat transfer performance of hybrid nanofluid in a horizontal pipe considering nanoparticles shapes effect

Abstract: In this paper, the problem of steady forced convection heat transfer and fluid flow characteristics of a hybrid nanofluid flowing through an isothermally heated horizontal tube considering various nanoparticle shapes has been investigated numerically. The three dimensionless cylindrical coordinate equations are discretized using the finite volume method and solved via a FORTRAN program. A numerical parametric investigation is carried out for a tube filled with regular water, (TiO 2 /water) nanofluid and (Ag-Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
35
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 53 publications
0
35
0
1
Order By: Relevance
“…They observed that in the presence of gold nanoparticles, the effect of thermal radiation on blood flow enhances the temperature, which aids in the drug delivery process to kill cancer cells. Benkhedda et al 8 presented the forced convection flow field dynamics of the hybrid nanofluid across an adiabatically warmed horizontal tube using the finite volume method. They recorded significant skin friction values for platelet‐shaped nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that in the presence of gold nanoparticles, the effect of thermal radiation on blood flow enhances the temperature, which aids in the drug delivery process to kill cancer cells. Benkhedda et al 8 presented the forced convection flow field dynamics of the hybrid nanofluid across an adiabatically warmed horizontal tube using the finite volume method. They recorded significant skin friction values for platelet‐shaped nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Montazer et al [11] described the development of the original relationships and the heat transfer of the stormy nanoparticles. Benkhedda et al [12] defined the horizontal tube considering the forms of nanoparticles, resulting in convective heat transfer presentation of the hybrid nanoparticles. Bhattad et al [13] conferred the plate in the heat exchanger of hydrothermal presentation of dissimilar alumina hybrid nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Applying additive nanoparticles to the base fluid to enhance the thermophysical properties of the working fluid has also been considered as an effective technique to modify heat transfer [ 12 , 13 ]. The hybrid nanofluids such as Ag–MgO–water [ 14 , 15 ], Ag–TiO 2 [ 16 ], Cu–Al 2 O 3 [ 16 , 17 ], and MgO–MWCNTs/EG [ 18 ] as well as using of nonencapsulated phase change material suspension [ 19 ] are also promising for enhancement of heat transfer. On the other hand, combining different techniques to promote the thermohydraulic performance of thermal engineering systems as much as possible has been paid a lot of attention in recent years [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%